Argentina's rejection of 2030 agenda undermines environmental sustainability and human well-being - Javier Nori; Alejandro E.J. Valenzuela; Micaela Camino; Elena Abraham; Gabriela Agostini; Marcelo A. Aizen; Virginia Alonso-Roldán; Julieta R. Arcamone; Yanina Arzamendia; German Baldi; Diego Baldo; Matías C. Baranzelli; et al. (Biological Conservation, 2024)

Exploring novel circulating biomarkers for liver cancer through extracellular vesicle characterization with infrared spectroscopy and plasmonics - R. Di Santo; F. Verdelli; B. Niccolini; S. Varca; A. del Gaudio; F. Di Giacinto; M. De Spirito; M. Pea; E. Giovine; A. Notargiacomo; M. Ortolani; A. Di Gaspare; et al. (Analytica Chimica Acta, 2024)

Effect of long-term compost fertilization on the distribution of organic carbon and nitrogen in soil aggregates - P. Gioacchini; E. Baldi; D. Montecchio; M. Mazzon; M. Quartieri; M. Toselli; C. Marzadori (CATENA, 2024)

Moving from ecological impacts to social vulnerability in data-scarce places - Matías E. Mastrangelo; Sebastián H. Villarino; M. Ximena Sirimarco; Sebastián Aguiar; Germán Baldi; Lucas Enrico; Laura Huaranca; María Vallejos (Journal of Environmental Management, 2024)

Exposure to pesticides and risk of Hodgkin lymphoma in an international consortium of agricultural cohorts (AGRICOH) - Joanne Kim; Maria E. Leon; Leah H. Schinasi; Isabelle Baldi; Pierre Lebailly; Laura E. Beane Freeman; Karl-Christian Nordby; Gilles Ferro; Alain Monnereau; Maartje Brouwer; Kristina Kjaerheim; Jonathan N. Hofmann; et al. (Cancer Causes & Control, 2023)
Purpose Some pesticides may increase the risk of certain lymphoid malignancies, but few studies have examined Hodgkin lymphoma (HL). In this exploratory study, we examined associations between agricultural use of 22 individual active ingredients and 13 chemical groups and HL incidence. Methods We used data from three agricultural cohorts participating in the AGRICOH consortium: the French Agriculture and Cancer Cohort (2005–2009), Cancer in the Norwegian Agricultural Population (1993–2011), and the US Agricultural Health Study (1993–2011). Lifetime pesticide use was estimated from crop-exposure matrices or self-report. Cohort-specific covariate-adjusted overall and age-specific (< 40 or ≥ 40 years) hazard ratios (HRs) and 95% confidence intervals (CIs) were estimated using Cox regression and combined using random effects meta-analysis. Results Among 316 270 farmers (75% male) accumulating 3 574 815 person-years at risk, 91 incident cases of HL occurred. We did not observe statistically significant associations for any of the active ingredients or chemical groups studied. The highest risks of HL overall were observed for the pyrethroids deltamethrin (meta-HR = 1.86, 95% CI 0.76–4.52) and esfenvalerate (1.86, 0.78–4.43), and inverse associations of similar magnitude were observed for parathion and glyphosate. Risk of HL at ≥ 40 years of age was highest for ever-use of dicamba (2.04, 0.93–4.50) and lowest for glyphosate (0.46, 0.20–1.07). Conclusion We report the largest prospective investigation of these associations. Nonetheless, low statistical power, a mixture of histological subtypes and a lack of information on tumour EBV status complicate the interpretability of the results. Most HL cases occurred at older ages, thus we could not explore associations with adolescent or young adult HL. Furthermore, estimates may be attenuated due to non-differential exposure misclassification. Future work should aim to extend follow-up and refine both exposure and outcome classification.

Native plant gardens support more microbial diversity and higher relative abundance of potentially beneficial taxa compared to adjacent turf grass lawns - Danielle S. Baldi; Christine E. Humphrey; John A. Kyndt; Tyler C. Moore (Urban Ecosystems, 2023)

Estimating genetic parameters of reproductive, carcass, and meat quality traits in Polled Nellore cattle - M. M. S. Mamede; G. J. M. Rosa; E. C. Eifert; F. B. Lopes; F. Baldi; M. F. Costa; R. D. Sainz; A. S. Carmo; A. S. Mascioli; C. U. Magnabosco (Tropical Animal Health and Production, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

A Role for Extracellular Vesicles in SARS-CoV-2 Therapeutics and Prevention - Jatin Machhi; Farah Shahjin; Srijanee Das; Milankumar Patel; Mai Mohamed Abdelmoaty; Jacob D. Cohen; Preet Amol Singh; Ashish Baldi; Neha Bajwa; Raj Kumar; Lalit K. Vora; Tapan A. Patel; et al. (Journal of Neuroimmune Pharmacology, 2021)

Social-Ecological Functional Types: Connecting People and Ecosystems in the Argentine Chaco - M. Vallejos; S. Aguiar; G. Baldi; M. E. Mastrángelo; F. Gallego; M. Pacheco-Romero; D. Alcaraz-Segura; J. M. Paruelo (Ecosystems, 2020)

Evaluation the of PL-PG-PA system in relation to quality of bovine milk - L. Rossi; F. Galante; E. Fusi; M. Luini; V. Dell’Orto; A. Baldi (Veterinary Research Communications, 2009)

Evaluation of the damage induced by ochratoxin A and the protective role of α-tocopherol in cultured bovine mammary epithelial cells - E. Fusi; R. Rebucci; C. Pecorini; L. Rossi; F. D’Ambrosio; A. Baldi (Veterinary Research Communications, 2008)

Effects of Rumen-protected Choline Supplementation in Periparturient Dairy Goats - F. D’Ambrosio; A. Campagnoli; F. Susca; E. Fusi; R. Rebucci; A. Agazzi; L. Pinotti; A. Baldi (Veterinary Research Communications, 2007)

Heterologous Expression of Biologically Active Porcine Lactoferrin in Pichia Pastoris Yeast - C. Pecorini; F. Savazzini; P. A. Martino; E. Fusi; C. Fogher; A. Baldi (Veterinary Research Communications, 2005)

Iron deficiency-induced changes in carbon fixation and leaf elemental composition of sugar beet (Beta vulgaris) plants - A. D. Rombolà; Y. Gogorcena; A. Larbi; F. Morales; E. Baldi; B. Marangoni; M. Tagliavini; J. Abadía (Plant and Soil, 2005)

A Preliminary Trial Using Multi-target Polymerase Chain Reaction (multiplex PCR) and Restriction Fragment Length Polymorphism (PCR-RFLP) on the Same Feedstuffs to Detect Tissues of Animal Origin - F. Colombo; E. Marchisio; I.E. Trezzi; V. Peri; L. Pinotti; A. Baldi; G. Soncini (Veterinary Research Communications, 2004)

Cloning and linkage mapping of resistance gene homologues in apple - P. Baldi; A. Patocchi; E. Zini; C. Toller; R. Velasco; M. Komjanc (Theoretical and Applied Genetics, 2004)

Milk Choline, α-Tocopherol and Neutrophil Chemotaxis in the Periparturient Dairy Cow - L. Pinotti; R. Rebucci; E. Fusi; L. Rossi; A. Baldi (Veterinary Research Communications, 2003)

DM235 (sunifiram): a novel nootropic with potential as a cognitive enhancer - Ghelardini C.; Galeotti N.; Gualtieri F.; Romanelli M.; Bucherelli C.; Baldi E.; Bartolini A. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2002)

Field assessments of gene flow from transgenic to cultivated rice (Oryza sativa L.) using a herbicide resistance gene as tracer marker - J. Messeguer; C. Fogher; E. Guiderdoni; V. Marfà; M. M. Català; G. Baldi; E. Melé (Theoretical and Applied Genetics, 2001)

Modeling coseismic displacements resulting from SAR interferometry and GPS measurements during the 1997 Umbria-Marche seismic sequence - S. Salvi; S. Stramondo; M. Cocco; M. Tesauro; I. Hunstad; M. Anzidei; P. Briole; P. Baldi; E. Sansosti; G. Fornaro; R. Lanari; F. Doumaz; et al. (Journal of Seismology, 2000)